Pore scale simulation of fluid flow and heat transfer in porous media - Ferreira de Sousa, Paulo (2013)
This paper presents an immersed boundary method for the calculation of fluid flow and heat transfer in porous media. A two-dimensional compact finite differences immersed boundary method was used to solve the unsteady, incompressible mass, momentum and energy conservation equations. The temporal and spatial discretizations are preformed, respectively, with a fourth-order Runge-Kutta method and a fourth-order compact scheme, used to achieve highly accurate calculations.